1999
DOI: 10.1097/00000658-199910000-00014
|View full text |Cite
|
Sign up to set email alerts
|

Minimally Invasive Surgery for Achalasia

Abstract: Minimally invasive techniques provided effective and long-lasting relief of dysphagia in patients with achalasia. The authors prefer the laparoscopic approach for three reasons: it more effectively relieved dysphagia, it was associated with a shorter hospital stay, and it was associated with less postoperative reflux. Laparoscopic Heller myotomy and partial fundoplication should be considered the primary treatment for esophageal achalasia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0
1

Year Published

2000
2000
2010
2010

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 348 publications
(35 citation statements)
references
References 8 publications
1
33
0
1
Order By: Relevance
“…One trial [25] assessed the efficacy of different endoscopic myotomy in achalasia patients. One-year remission rate of patients was 89% in laparoscopic myotomy and 73% in thoracoscopic (P = 0.1).…”
Section: Laparoscopic Myotomy Versus Thoracoscopic Myotomymentioning
confidence: 99%
See 1 more Smart Citation
“…One trial [25] assessed the efficacy of different endoscopic myotomy in achalasia patients. One-year remission rate of patients was 89% in laparoscopic myotomy and 73% in thoracoscopic (P = 0.1).…”
Section: Laparoscopic Myotomy Versus Thoracoscopic Myotomymentioning
confidence: 99%
“…The most severe complication with pneumatic dilation is perforation. One study reported a higher complication rate of GER after thoracoscopic myotomy (21/35 patients, 67%) than after laparoscopic myotomy (23/133, 17%; P \ 0.03) [25].…”
Section: Complications and Adverse Eventsmentioning
confidence: 99%
“…These rates were apparently higher than those seen in previous reports: 6.7–17% of postoperative patients [14,15,16]. Tatum et al [7] mentioned that patients with achalasia might be less sensitive to significant gastroesophageal reflux than the general population.…”
Section: Discussionmentioning
confidence: 69%
“…19 Publications on failure of laparoscopic myotomy and the need for reoperation include fewer patient numbers and shorter follow-up, if reported at all. [26][27][28]30,32,[34][35][36] One of the two largest series on laparoscopic reoperation reported on by Iqbal et al comprised 11 patients with achalasia 3 (others included had hypertensive lower esophageal sphincter and one had DES) and showed an overall symptom resolution of 40-89%. 30 In this study, the interval between the first and the second operation was rather short with a mean of 23 (3-52) months and a mean follow-up of 30 months.…”
Section: Methodsmentioning
confidence: 99%